Replikasi Kalkulator Deteksi Stunting dalam Program Gerabah Stunting Manis melalui Kolaborasi Pentahelix oleh DP2KBP3A Kabupaten Ciamis - Suminar, Ratna; Budiyana, Dian; Rohita, Tita; Heryani, Heni (Yayasan Inspirasi El Burhani, 2025)
Introduction: Stunting remains a significant public health issue that requires a multisectoral and community-based approach. Local government initiatives supported by cross-sectoral collaboration are key to accelerating stunting reduction efforts, especially through the optimization of local wisdom and community empowerment. One of the strategic tools utilized in this program is the Stunting Detection Calculator (Kalkulating). Objective: This community service aimed to replicate the use of the Kalkulating platform in the implementation of the Gerabah Stunting Manis program through a pentahelix collaboration initiated by the DP2KBP3A of Ciamis Regency across five target sub-districts. Method: The program was carried out through district-level community dialogues (saresehan) from January 9–16, 2025, followed by village-level sessions from February 10–17, 2025, in five selected villages. The program included seven stages of mentoring and integrated Kalkulating for stunting risk screening in toddlers and adolescents. Data were collected through direct observation, screening results, interviews with stakeholders, and village reports. Result: The activity involved 63 community health volunteers (Posyandu cadres), 25 prospective brides and grooms, 114 pregnant women, 40 postpartum mothers, and 440 toddlers. Each village developed localized innovations as strategies to prevent stunting. Stakeholder collaboration was reflected in the involvement of various government agencies, academics, and the community. Conclusion: The replication of the Kalkulating platform in the Gerabah Stunting Manis program successfully strengthened early stunting risk detection while fostering the emergence of local innovations. The sustainability of this program requires continued cross-sectoral synergy, program integration, and active community participation.